ANALISIS PENGARUH KUALITAS PELAYANAN ONLINE TERHADAP KEPUASAN PELANGGAN PADA TOKO YUIKAASHOP - Rahmadany stie bima; Irma Mardian; Muhajirin Muhajirin (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Bima, 2025)
In Fulfilling Customer Satisfaction, Service Quality becomes a reference for consumers in making purchasing decisions. The aim of this research is to determine the partial effect of online service quality on customer satisfaction. The type of research is associative. The research instrument used a questionnaire with a Likert scale. The population used in this research is all consumers who have made purchases at the Yuikashop Store, the number of which is not known for certain (unknown population). The number of samples used in this research was 50 respondents with a sampling technique, namely purposive sampling. Data collection techniques use observation, questionnaires and literature study. Data analysis techniques include validity tests, reliability tests, simple linear regression tests, determination tests, and t tests. The results of this research indicate that online service quality has a significant effect on customer satisfaction.